The perception of tertiary students in UiTM Kota Kinabalu towards rape victims / Frederic David and Brian Melchior Basusie - David, Frederic; Basusie, Brian Melchior (2016)
Rape is a heinous crime by itself. The act of forcing sexual advances onto another without consent is generally considered by the public as a common definition of rape. Malaysia has a recorded of 31,685 rape cases between the year 2000 to 2013 - with 2,111 cases involving underage rape victims. Though, this study, while will discuss on the issue in general, will specifically explore on the perceptions of how rape victims and rape itself is viewed at large. The present study was conducted within the confines of UiTM Sepanggar - Sabah's campus, consisting of both degree and diploma students from different faculties. Finding shows that gender-based perceptions is a strong variable — supporting previous studies; while ethnic-cultural and religious based perceptions provided the least impact towards affecting perceptions.